Pengembangan Aplikasi Penyedia Buku Online Berbasis Android Menggunakan Metode Prototyping (Studi Kasus: Universitas Brawijaya) - Linda Shintya Sari; Adam Hendra Brata; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Books become one of the source of information, reading books can increase literacy for everyone. However, Literacy culture in the city of Malang is still low, to increase people's interest in reading, Jendela Malang community was formed, is a community to increase children's interest in reading, besides also receiving books donation that will be donated to orphanages or special schools. Brawijaya University students also have a need for books to support the lecture process, by buying books they need, or borrow from friends. For books that are not used, students can collect or donate books. The problems that exist in students are the lack of relationships that are willing to make book transactions and the lack of information to find book owner of the book that suit their needs, and being late in returning books, meanwhile the problem faced by the Jendela Malang Community is that they cannot select books to be received. The solution to this problem is to develop a android mobile-based application as a book provider that function to exchange, borrow, or donate books to the Jendela Community. From the requirement analysis resulted in 28 functional needs and 2 non-functional needs, which were developed using the prototyping method with two iterations. The results of the design will be implemented then tested using 4 tests. From the 3 functions tested by unit testing and of 28 functional requirements that were tested by validation testing obtained valid results that the application was developed according to the requirements that have been defined, from compatibility testing obtained valid results that the application can run on Android versions of Lollipop to Pie, and usability testing the SUS value of 75 is acceptable.